Validitas Instrumen Penilaian Kinerja Keterampilan Proses Sains pada Mata Pelajaran Biologi SMA - Aulia Hermawati Ulfah; Supahar (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2026)
This study aims to develop an assessment instrument for measuring science process skills among 10th-grade high school students in Biology. The research adopts a quantitative approach, involving a sample of 415 high school students from Sumedang Regency. Participants were selected from four high schools based on the 2022 Minimum Competency Assessment (AKM) evaluation criteria. Data analysis included content validity using Aiken’s V and construct validity through Confirmatory Factor Analysis (CFA). A total of 36 items were validated by six experts, including measurement specialists, subject matter experts, and high school Biology teachers. Based on the validators’ feedback, several items were revised, and one item was removed, resulting in 35 items being tested. The Aiken’s V validity index was >0.78. trial data were used to establish construct validity, with CFA tested against Goodness of Fit criteria, including GFI, RMSR/RMR, TLF/NNFI, CFI, IFI, AGFI, and RMSEA. After model modification, all items met the fit criteria of 30 items, proven valid for assessing science process skills among 10th-grade high school students in Biology.